Preferences and Experiences of Family Members Witnessing Cardiopulmonary Resuscitation: A Systematic Review - Karaçay, Pelin; Doğu, Özlem (Türk yogun bakim dergisi, 2020)
Bu sistematik derlemenin amacı, kardiyopulmoner resüsitasyona tanık olan aile üyelerinin tercihlerini ve deneyimlerini incelemektir. Cochrane, JBI, Ovid, PubMed, Scopus ve Web of Science elektronik veri tabanlarında taramalar yapıldı. Sistematik incelemeye 2013-2018 yılları arasında yetişkin hastalar ve aile üyeleri ile yürütülen ve hakemli dergilerde İngilizce olarak yayınlanan çalışmalar dahil edildi. Kapsama alınan makaleler araştırmacılar tarafından bağımsız olarak özetlendi ve fikir birliği sağlandı. Toplam dokuz çalışma dahil edildi. Aile üyeleri kardiyopulmoner resüsitasyona tanık olmak istemekte ve bu karara sağlık profesyonelleri tarafından saygı gösterilmesini beklemektedirler. Sınırlı sayıda çalışma olmasına rağmen, kardiyopulmoner resüsitasyona tanık olan aile üyelerinin daha az kaygı, depresyon, travma sonrası stres ve keder yaşadığı belirlendi. Kardiyopulmoner resüsitasyona tanık olan aile üyelerinin olumlu ve olumsuz deneyimlerini belirlemek için daha fazla karşılaştırmalı araştırmalara ihtiyaç vardır. This systematic review aimed to examine the preferences and experiences of family members who had witnessed cardiopulmonary resuscitation. Electronic searches were performed on Cochrane, JBI, Ovid, PubMed, Scopus, and Web of Science. We included studies conducted among adult patients and family members that were published in peer-reviewed journals in English between 2013-2018. The studies were summarized by the researchers independently. Then, the summaries were compared, and a consensus was established among the researchers. A total of nine studies were included. Family members expressed that they wanted to witness the cardiopulmonary resuscitation and expected to have that decision respected by healthcare professionals. Although the number of studies were limited, family members who had witnessed cardiopulmonary resuscitation experienced less anxiety, depression, post-traumatic stress, and grief. Further comparison studies are needed to identify the positive and negative experiences of family members who witnesss cardiopulmonary resuscitation.